The Yin and Yang of Current Antifungal Therapeutic Strategies: How Can We Harness Our Natural Defenses? - Di Mambro, Tomas; Guerriero, Ilaria; Aurisicchio, Luigi; Magnani, Mauro; Marra, Emanuele (Frontiers in Pharmacology, 2019)
Fungal infections have aroused much interest over the last years because of their involvement in several human diseases. Immunocompromission due to transplant-related therapies and malignant cancer treatments are risk factors for invasive fungal infections, but also aggressive surgery, broad-spectrum antibiotics and prosthetic devices are frequently associated with infectious diseases. Current therapy is based on the administration of antifungal drugs, but the occurence of resistant strains to the most common molecules has become a serious health-care problem. New antifungal agents are urgently needed and it is essential to identify fungal molecular targets that could offer alternatives for development of treatments. The fungal cell wall and plasma membrane are the most important structures that offer putative new targets which can be modulated in order to fight microbial infections. The development of monoclonal antibodies against new targets is a valid therapeutic strategy, both to solve resistance problems and to support the immune response, especially in immunocompromised hosts. In this review, we summarize currently used antifungal agents and propose novel therapeutic approaches, including new fungal molecular targets to be considered for drug development.